2012
DOI: 10.1016/j.taap.2012.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Ahr2-dependence of PCB126 effects on the swim bladder in relation to expression of CYP1 and cox-2 genes in developing zebrafish

Abstract: The teleost swimbladder is assumed a homolog of the tetrapod lung. Both swimbladder and lung are developmental targets of persistent aryl hydrocarbon receptor (AHR1) agonists; in zebrafish (Danio rerio) the swimbladder fails to inflate with exposure to 3,3’,4,4’,5-pentachlorobiphenyl (PCB126). The mechanism for this effect is unknown, but studies have suggested roles of cytochrome P4501 (CYP1) and cyclooxygenase 2 (Cox-2) in some Ahr-mediated developmental effects in zebrafish. We determined relationships betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 68 publications
3
30
0
Order By: Relevance
“…Malformation of the swim bladder has been a characteristic indicator of developmental toxicity demonstrated in many species of fishes in response to numerous types of waterborne chemicals, e.g., disinfectants (Sanabria et al, 2009), biphenyls (Jönsson et al, 2012), herbicides (González-Doncel et al, 2008), and even urban storm water run-off (Skinner et al, 1999). This condition may be attributed to compounds that alter the air-water interface, like oil itself.…”
Section: Discussionmentioning
confidence: 99%
“…Malformation of the swim bladder has been a characteristic indicator of developmental toxicity demonstrated in many species of fishes in response to numerous types of waterborne chemicals, e.g., disinfectants (Sanabria et al, 2009), biphenyls (Jönsson et al, 2012), herbicides (González-Doncel et al, 2008), and even urban storm water run-off (Skinner et al, 1999). This condition may be attributed to compounds that alter the air-water interface, like oil itself.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue localization of COX2b, as well as COX2a, should be examined in future studies, A single study reported that COX2a was detected within sprouting gill arteries and vasculature of the intestine of 4 dpf eleutheroembryos (Grosser et al, 2002). Recently, it was reported that PCB126 induced both COX2a and COX2b in 4 dpf eleutheroembryos (Jönsson et al, 2012), which is reminiscent of the results of Dong et al (2010), who reported COX2 induction by TCDD and the correlation between COX2 induction and pericardial edema in developing medaka. The present results provide important evidence for the involvement of COX2b in precardiac edema formation around heart by TCDD.…”
Section: Discussionmentioning
confidence: 53%
“…qRT-PCR analysis was performed in Real-Time PCR Detector (Chromo4: Bio-Rad, Hercules, CA) using Thunderbird qPCR mix containing SYBR Green (Toyobo, Osaka, Japan). The same primers as reported in Jönsson et al (2012) were used; COX2b (GenBank ID: NM_001025504.2): F-GGCTCATCCTTATTGGTGAGACTAT and R-TCGGGATCAAACTTGAGCTTAAAATA (5' to 3' sequences), and COX2a (GenBank ID: NM_153657.1): F-ACTACCCCTGAGCTTCTCACA and R-GATGCTGTTGATGATATCCCAGATTG.…”
Section: Methodsmentioning
confidence: 99%
“…The latter was selected as a reference chemical as it represents one of the most abundant planar polychlorobiphenyl which can be found in the ng/L range in the environment (Ge et al, 2014). Moreover, its toxicity during zebrafish development is well described (Brown et al, 2002;Grimes et al, 2008;Jonsson et al, 2007a;Jonsson et al, 2012;Liu et al, 2015;. PCB126 is recognized as a strong inducer of biotransformation enzymes (i.e.…”
Section: Introductionmentioning
confidence: 99%